Psoriatic epidermis expresses high level of inflammatory mediators and the CDK2/4 cyclin‐dependent kinases are involved in the regulation of cell‐cycle progression in epidermal cells. (11th December 2019) - Gesser, B.; Rasmussen, M.K.
Abstract : Linked Article : Henri et al . Br J Dermatol 2020; 182: 678–689 .